Positive Solutions of a Fractional Boundary Value Problem with Changing Sign Nonlinearity - Yongqing Wang; Lishan Liu; Yonghong Wu (Abstract and Applied Analysis)
We discuss the existence of positive solutions of a boundary value problem of nonlinear fractional differential equation with changing sign nonlinearity. We first derive some properties of the associated Green function and then obtain some results on the existence of positive solutions by means of the Krasnoselskii's fixed point theorem in a cone.